Influence of chisel share for the destruction of concrete - Peldschus, Friedel; Wild, Jens-Thorsten (Journal of Civil Engineering and Management, 2003)
The energy shares occurring in the chiselling process were investigated in order to increase the productivity of the manual destruction of concrete. Apart from the influences of notch energy and cleaving energy, the energy loss due to friction forces was considered. As a result two new chisel forms were developed as a combination of sharp cutting edge and steep wedge. The effectiveness of these chisels was tested under experimental conditions as well as under reality conditions. It was found that the application of lateral tips at the chisel leads to an improved processing performance. First Published Online: 26 Jul 2012